Research on the Diversified and Collaborative Prevention and Resolution of Disputes (Journal of humanities and social sciences exploratio, 2025)
Taking "diversified and collaborative governance of disputes" as its central theme, the article sequentially examines its theoretical foundations, practical drivers, and operational solutions. Drawing on collaborative governance, social network, and polycentric theories, it first explains the institutional potential of multi-actor responses to complex conflicts. It then uses leading domestic cases to distill their operational logic and performance. Empirical analysis shows that current collaborative governance is still constrained by fragmented inter-agency cooperation, uneven civil-society development, and limited deep public participation. Accordingly, the paper offers systematic improvements from four dimensions—institutional integration, capacity building, participation expansion, and technological empowerment—to enhance dispute-resolution efficiency and advance the modernization of the social-governance system and the building of a harmonious society.
Keywords: Disputes; Prevention and resolution; Pluralistic governance; Collaborative governance; Social governance